Analysis of the Implementation of Sustainable Business for Cooperative Reputation (Case Study in South Tangerang) - Muhammad, Nashar (Economics and Business Solutions Journal, 2020)
Cooperatives as one of the drivers of the community's economy face many obstacles in its performance. Poor performance, incompetent human resources, and financial system that is still not good to be a fundamental weakness in the ability of cooperatives to compete in economic activities that are full of challenges today. Of the 150,333 cooperatives in Indonesia the level of success and sustainability of cooperatives is still very small. This study aims to analyze the application of sustainable business to cooperative reputation.in South Tangerang City   Data Analysis Method uses Structural Equation Modeling-Partial Least Square (SEM-PLS).The Result of study The relationship between economic aspects and sustainable business is positive and significant. Relationship between social aspects and sustainable business is positive and significant. Relationship between environmental aspects and sustainable business is positive and significant. The relationship between Sustainable business and the reputation of the cooperative is positive and significant
Keywords: Sustainable business; reputation of cooperatives; South Tangerang cooperatives